"As the Test Collapses In": Teaching and Learning Amid High-Stakes Testing in Two Urban Elementary Classrooms. (July 2023) - Hikida, Michiko; Taylor, Laura A.
Although there is much research detailing the pedagogical constraints of high-stakes testing (HST), there is less that examines teachers' practices within and beyond its control. This multiple case study analyzes ethnographic data to explore two teachers' practices in an urban context where HST was relevant. Drawing on Foucault's conceptualization of a plague-stricken town, we explore the mobilization of disciplinary power associated with HST. We then examine teachers' agency as they taught beyond the administrative gaze. We found that teachers sometimes complied with administrative mandates while also articulating tensions of providing access and actively resisting/critiquing the test.